Penerapan Metode Bermain Peran untuk Meningkatkan Kemampuan Berbicara - Nuryati Nuryati; Rangganis Rangganis (Jurusan Pendidikan Islam Anak Usia Dini, 2022)
This study aims to find out the application of the role-playing method for speaking skills in children aged 5-6 years at PAUD BKB HI Kutilang, Petir District, Serang Regency, Banten. The type of research used in this research is Classroom Action Research (CAR). The subjects in the study were children aged 5-6 years at PAUD Kutilang, totaling 12 children. Data collection was taken from observation sheets, interviews, and documentation. This research method has been implemented in two cycles of activities. Based on the results of the research and discussion that has been carried out, it is concluded that the role playing method can improve the speaking ability of children aged 5-6 years in PAUD BKB HI Kutilang, experiencing a very significant increase from the beginning of the pre-cycle with low results and in the second cycle which experienced the increase from the first cycle which increased very significantly. The increase in speaking ability can be seen from the percentage of data obtained in pre-action, Cycle I and Cycle II. At the pre-action stage, most of the children were included in the criteria for not yet developed, which was 43.75%, in the first cycle the children's speaking ability increased in the criteria for starting to develop with the total percentage score of the first cycle of 56.95%. In the second cycle of action increased to 70.83%. Learning is said to be successful because children's writing skills have increased by more than 70% from the initial conditions before the action and are in accordance with predetermined success indicators.